Blocking retinoic acid receptor-α enhances the efficacy of a dendritic cell vaccine against tumours by suppressing the induction of regulatory T cells - GALVIN, KAREN; HIGGINS, SARAH; MILLS, KINGSTON; STEFANSKA, ANNA; MORAN, BARRY; DUNGAN, LARA (My University, 2013)
The immune system has evolved regulatory mechanisms to control immune responses to self-antigens. Regulatory T (Treg) cells play a pivotal role in maintaining immune tolerance, but tumour growth is associated with local immunosuppression, which can subvert effector immune responses. Indeed, the induction and recruitment of Treg cells by tumours is a major barrier in the development of effective immunotherapeutics and vaccines against cancer. Retinoic acid (RA) has been shown to promote conversion of naïve T cells into Treg cells. This study addresses the hypothesis that blocking RA receptor alpha (RARα) may enhance the efficacy of a tumour vaccine by inhibiting the induction of Treg cells. We found that RA significantly enhanced TGF-β-induced expression of Foxp3 on naïve and committed T cells in vitro and that this was blocked by an antagonist of RARα (RARi). In addition, RARi significantly suppressed TGF-β and IL-10 and enhanced IL-12 production by dendritic cells (DC) in response to killed tumour cells or TLR agonists. Furthermore, RARi augmented the efficacy of an antigen-pulsed and TLR-activated DC vaccine, significantly attenuating growth of B16 tumours in vivo and enhancing survival of mice. This protective effect was associated with significant reduction in tumour-infiltrating FoxP3(+) and IL-10(+) Treg cells and a corresponding increase in tumour-infiltrating CD4(+) and CD8(+) T cells that secreted IFN-γ. Our findings demonstrate that RARα is an important target for the development of effective anti-tumour immunotherapeutics and for improving the efficacy of cancer vaccines.
PUBLISHED
Keywords: Tumour immunity; Cancer; Immunology, Inflammation & Infection